PENGARUH MODEL PROJECT BASED LEARNING (PJBL) DALAM PENGUATAN PROYEK PROFIL PELAJAR PANCASILA TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK SD MUHAMMADIYAH MIMBAR - Annisa Maqfira; Nursalam; Syarifah Aeni Rahman (STKIP Subang, 2025)
The research is a quantitative research with a pre-experimental one group pretest-posttest design that aims to determine the application of the Project-based Learning (PjBL) model in the Pancasila Student Profile Strengthening Project (P5), to determine the differences in student character before and after the application of the Project-based Learning model, and to analyze the influence of the Project-based Learning model on the character formation of students at Muhammadiyah Mimbar Elementary School. The research subjects were 19 students of class IV B involved in a project with the theme